INTERLEUKIN-1?, INTERLEUKIN-6, AND ANTAGONIST INTERLEUKIN-1RECEPTOR AS MEMORY IMPAIRMENT RISK FACTOR IN COMPLEX PARTIAL EPILEPSY - Purwa-Samatra, D. P. G.; Sudewa-Djelantik, A. A. G.; Suastika,; K. (Udayana University, 2013)
Memory impairment is one of the most common adverse following epilepsy, particularly complex partial epilepsy. Cytokines physiologically play an important role in memory impairment by preventing long term potentiation process in hypocampus. Several literatures have mentioned that IL-1b, IL-6 and antagonist receptor IL-1Ra are crucial cytokines in complex partial epilepsy. This study aims to find out whether high level of IL-1b and IL-6 as well as low level of IL-1Ra might be risk factors of memory impairment in complex partial epilepsy patient. This was a case control study, enrolling 30 complex partial epilepsy patients with memory impairment as case group and 30 complex partial epilepsy patients without memory impairment as control group. In this study, it was obtained that the mean of IL-1? level in case group was significantly higher compared to the control (2.74 ± 4.36 vs. 0.42 ± 0.18 pg/ml, p = 0.007). The mean of IL-6 in case group was significantly higher compare to control (5.89 ± 6.32 vs. 2.34 ± 1.80 pg/ml, p = 0.006). The mean of IL-1Ra level of the case group was not significantly higher compared to the control (519.81 ± 262.64 vs. 413.28 ± 106.85, p = 0.767). By applying bivariate analysis, McNemar’s test, we observed that IL-1? with cut off point 0.63 pg/ml and OR = 70 is a risk factor of memory impairment in complex partial epilepsy indicated by p = 0.001. Similar result was also gained for IL-6 with cut off point 2.87 pg/ml and OR = 4.57 as a risk factor of memory impairment in complex partial epilepsy indicated by p = 0.007. Meanwhile, IL- 1Ra with cut off point 471 pg/ml and OR = 0.727 was not as a risk factor of memory impairment in complex partial epilepsy indicated by p = 0.573. It can be concluded that the high level of IL-1B and IL-6 were the risk factors of memory impairment in complex partial epilepsy patients. High level 1L-1B patient was 70 times higher risk of becoming memory impaired. High IL-6 patients will have the risk nearly 5 times higher. The low level of IL-1Ra does not as a risk factor in epilepsy patients for having the following memory impairment.